Patient-reported perceptions of care after the introduction of a new advanced cancer nursing role in Sweden. (August 2019) - Westman, B.; Ullgren, H.; Olofsson, A.; Sharp, L.
Abstract: Purpose: Extensive research results show quality improvements associated with advanced cancer nursing roles. Despite this, these roles are not implemented in many countries. The aim of this cross-sectional, population-based study was to compare patients' perception of care, before and after the introduction of a new advanced nursing role, the coordination contact nurse (CCN), in a region in Sweden. Method: All patients (with gynaecological, haematological, Head & Neck, upper gastrointestinal cancers) diagnosed in the region the year prior and one-year post introducing the new CCN role were identified from the Swedish Cancer Register. Data were collected using the European Organization of Research and Treatment of Cancer [EORTC] Quality of Life Questionnaire (QLQ-C30 and QLQ-INFO25) and a study specific questionnaire. Result: The results, based on baseline (n = 869) and follow-up data (n = 1003), show statistically significant patient-reported improvements after the introduction of the CCN role, regarding health-related patient information (EORTC QLQ- INFO25 global mean score increased from 41.23 to 44.16, p = 0.0006). We found statistically significant improvements related to availability of supportive care resources, e.g. increased reported access to contact nurse (from 53% to 66%, p ≤ 0.0001) and individual written care plans (from 40% to 54%, p < 0.0001). We also found some improvements related to patient involvement and care coordination, but also room for further developments. Conclusion: The implementation of the new advanced cancer nursing role may have contributed to important improvements, but it has also identified areas in need of development. Further research with long-term evaluations of CCN roles in other contexts, are both needed and on-going. Highlights: The introduction of a new cancer nursing role contributed to patient-reported improvements. The improvements mainly concerned patient information and access to supportive care resources. The new role impacted less on patient involvement and coordination of care.